Artificial Intelligence-Driven Water Governance: Intellectual Property Protection and Climate-Resilient Water Management in Pakistan - Hammad Khan; Aamir Akhtar (`, 2026)
Water scarcity and climate change present critical governance challenges for Pakistan, particularly in provinces such as Khyber Pakhtunkhwa where agricultural dependence, rapid population growth, and environmental variability intensify pressure on limited water resources. Recent technological developments suggest that artificial intelligence (AI) can play a transformative role in improving water governance through predictive analytics, smart irrigation systems, real-time monitoring, and decision-support platforms. At the same time, the expansion of AI-driven environmental technologies raises important questions regarding intellectual property protection, technology diffusion, and regulatory oversight. This study examines the intersection of artificial intelligence innovation, intellectual property frameworks, and climate-resilient water governance in Pakistan. Using a qualitative doctrinal and policy analysis, the research evaluates how AI technologies can strengthen water management systems while considering the legal and institutional structures that regulate technological innovation and access. The study analyzes existing literature on AI-based environmental governance, reviews Pakistan’s water management policies, and explores the implications of intellectual property protection for the development and deployment of AI-enabled water technologies. The findings suggest that AI applications have significant potential to enhance climate resilience through improved forecasting, efficient resource allocation, and data-driven governance mechanisms. However, institutional fragmentation, limited technological infrastructure, and insufficient intellectual property governance may hinder effective implementation. The paper argues that a balanced regulatory framework promoting innovation while ensuring equitable access to climate technologies is essential for sustainable water governance. Strengthening policy coordination, promoting open innovation models, and encouraging public–private partnerships are recommended to support the integration of AI technologies into Pakistan’s water management systems and advance long-term climate resilience. https://doi.org/10.5281/zenodo.19006159